Remote Sensing of Evapotranspiration in a Southern Mediterranean Forest. Application to Bissa Forest, Algeria - Adda, Ababou; Mohammed, Chouieb; Djamel, Saidi; Abdelkader, Bouthiba; Khalladi, Mederbal (The International Journal of Biotechnology, 2016)
The Simplified Surface Energy Balance Index (S-SEBI) algorithm was used in this study with four Landsat-5 Thematic Mapper images to assess the evapotranspiration (ET) in Bissa forest, one of the healthiest Algerian forests located south of the Mediterranean Sea. Results showed that ET varies over the different seasons, the highest ET values were reached during the spring due to water availability, whereas, the lowest values were recorded during the summer. The relationship between normalized difference vegetation index (NDVI) and ET showed that the highest ET values coincide always with the highest NDVI except for January where even the lowest NDVI values correspond to higher ET. The intensity of ET was closely related to aspects, southeastern exposures showed the highest ET, whereas, northwestern exposures showed the lowest ET.